Labour, environment, and globalisation : social clause in multilateral trade agreements : a southern response - John, J.; Chenoy, Anuradha M.; Centre for Education and Communication (New Delhi, India) (New Delhi : New Age International (P) Ltd. Publishers, 1996)
Contributed articles.
"Centre for Education and Communication."
Includes bibliographical references and index.
Keywords: Uruguay Round -- (1987-1994); World Trade Organization; Foreign trade and employment -- India; Labor laws and legislation -- India; Labor laws and legislation, International; Free trade -- Environmental aspects; India -- Foreign economic relations; India -- Commercial treaties -- Social aspects